1964
DOI: 10.1021/bi00897a005
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on the Modification of Myosin Nucleosidetriphosphatase*

Abstract: In the sense that they activate the 25" Ca*+-adenosine-5'-triphosphatase, inhibit the 25" Ca*+inosine-5'-triphosphatase, and inhibit the 0' activity of both nucleosidetriphosphatases, dioxane and hydrogen peroxide are true "modifiers" of myosin nucleosidetriphosphatase. Modification by peroxide, as by p-mercuribenzoate, clearly involves reaction of certain myosin sulfhydryl groups, but no compelling evidence for sulfhydryl involvement was found in modification by dioxane, and there was found some direct eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
26
0

Year Published

1965
1965
1994
1994

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 20 publications
3
26
0
Order By: Relevance
“…White and Rayment (3) have reported that such methylation markedly increases the Mg2+-ATPase activity of S-1, in a manner kinetically similar to that produced by attaching a bulky group to Cys-707 (4,5). Do the seemingly disparate modulations such as those induced by generalized lysine methylation, modification of Cys-707, transition from pH 7.5 to 9.2, and many other agencies (6, 7) share a common feature with one another and perhaps with F-actin binding? Here we have studied three intentionally disparate modulations-methylation, alkylation of Cys-707, and the pH transition.…”
mentioning
confidence: 99%
“…White and Rayment (3) have reported that such methylation markedly increases the Mg2+-ATPase activity of S-1, in a manner kinetically similar to that produced by attaching a bulky group to Cys-707 (4,5). Do the seemingly disparate modulations such as those induced by generalized lysine methylation, modification of Cys-707, transition from pH 7.5 to 9.2, and many other agencies (6, 7) share a common feature with one another and perhaps with F-actin binding? Here we have studied three intentionally disparate modulations-methylation, alkylation of Cys-707, and the pH transition.…”
mentioning
confidence: 99%
“…What actually happens in modification? Several authors (166)(167)(168) found that modification of Ca 2 + ATPase can also be produced by moderate con centrations of organic solvents. It was found (169, 170) that modification could be sensed by an accompanying increase in fluorescence intensity of ANS bound to myosin, or by a decrease in energy transferred to ANS by a vicinal Trp.…”
mentioning
confidence: 99%
“…Because the binding ofactin, ATP, and other polyphosphates to the myosin head is known to produce conformational changes at identifiable sites (6-10) and because conformational changes induced elsewhere by putting bulky substitutes at SH1 (11) or by organic solvents (12,13) produce changes at the ATPase site, we decided to study whether these conformational changes extend to the newly described 2500-Dal hinge region. In this paper we present evidence that ATP and its derivatives and various reaction conditions affect the conformation ofthe 2500-Dal hinge region.…”
mentioning
confidence: 99%